In vivo time‐resolved X‐ray fluorescence mapping measurements of Egeria densa immersed in Cr(VI) aqueous solution. (30th June 2014) - Hayashi, Hisashi
<x xml:space="preserve">Abstract</x> In vivo time‐resolved Cr and Ca X‐ray fluorescence (XRF) mapping measurements were performed in a laboratory over a period of 69 days on a living common aquatic plant Egeria densa that was immersed in 5 mM K2CrO4 aqueous solution. The time and spatial resolution for each time‐resolved XRF map were ~1.6 days and 1 × 1 mm2, respectively. The obtained XRF maps exhibited characteristic localized Cr and Ca areas where the XRF signals were especially strong ('hot spots'), and this indicated the necessity of preliminary millimeter‐resolution surveying in XRF microscopy. Ca hot spots were detected prior to Cr(VI) immersion and nearly disappeared after immersion in deionized water for 2 weeks and the Cr(VI) solution for 1 week. After these immersions, a Cr hot spot was formed at approximately the same location of the missing Ca hot spot, which suggests that the original Ca‐accumulated regions were substituted for the isolation of Cr species when they were introduced. The sizes and intensity distributions of the Cr hot spots were sensitive to the Cr(VI) exposure approximately 1 week prior to each XRF measurement. This sensitivity suggests potential applications of E. densa as a Cr(VI) biomonitor in aquatic environments. Copyright © 2014 John Wiley & Sons, Ltd.